The Influence of the Ability to Manage Job Stress, Person Job Fit, and Work Relations on Employee Loyalty and Job Satisfaction as a Moderation Variable in Employees PT. Sreeya Sewu Indonesia Tbk Slaughterhouse Division - Junita Hutabarat; Faisal Marzuki; Mahendro Sumardjo; Iwan Kresna Setiadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research is conducted to examine the effect of several key organizational factors on employee loyalty, specifically focusing on the ability to manage work stress, person-job fit, and the quality of work relationships. Additionally, this study investigates the role of job satisfaction as a moderating variable that may strengthen or weaken the relationship between these factors and employee loyalty. The study is centered on employees working at PT. Sreeya Sewu Indonesia Tbk, specifically within the Slaughterhouse Division. A quantitative research method is employed to ensure objectivity and statistical validity. The sample for this research consists of 100 employees, selected through a simple random sampling technique to represent the larger employee population fairly. Data collection was carried out through a structured questionnaire distributed digitally using Google Forms, allowing for efficient and widespread distribution. To analyze the data, this research utilizes the Partial Least Squares (PLS) method with the assistance of SmartPLS version 4 software. The use of PLS is appropriate for testing complex relationships between latent variables and for predictive modeling. Through this approach, the research aims to provide valuable insights into how stress management capabilities, job fit, and interpersonal dynamics contribute to fostering loyalty among employees, moderated by the level of job satisfaction.